Corrosion behavior of Ni-base alloy C276 in supercritical water - SHEN Chao; WANG Jia-mei; ZHANG Le-fu (工程科学学报, 2016)
This article is focused on the corrosion behavior of Ni-base alloy C276 exposed to 550-650℃/25 MPa supercritical water. The oxidation kinetics,oxide morphology,element distribution and structure of the oxide film were analyzed by using weight gain measurement,scanning electron microscopy,energy spectrometry,and X-ray diffraction analysis. It is shown that C276 alloy exhibits general corrosion in the supercritical water,and the weight gain is subject to parabolic growth kinetics. The weight gain of C276 alloy at 600℃ is approximately three times that of C276 alloy at 550℃,while the weight gain shows a decline when the temperature increases to 650℃. The oxide film is not distinguishable and is mainly consisted of(Ni,Fe) Cr2O4. A large number of Ni O oxide particles are observed on the oxide film. The protective ability of the oxide film is dependent upon Cr content,and the higher the Cr content,the better the protective ability is.